Spatial Analysis of the Impact of Population Density on Health Facilities in Nanggalo District Padang City - Irfan, Irfan; Dasrizal, Dasrizal; Zuriyani, Elvi (Universitas Lambung Mangkurat, 2024)
The type of research used in this research is quantitative descriptive. The population in this study is the distribution of health facilities in Nanggalo District. Sampling in this study used total sampling with a sample of all health facility objects in Nanggalo District. The results of this research can be concluded that 1) The total distribution of health facilities in Nanggalo District is 17 units consisting of 11 pharmacies, 4 clinics and 2 health centers. Coordinates are taken directly in the field to find the exact location using the Global Position System (GPS) application. 2) The population density level of Nanggalo sub-district is 7438 people/km² with an area of 8.07 km². Tabiang Banda Gadang Village has a density of 7007 people/Km², Gurun Lawas Village has a density of 4352 People/Km², Kampung Olo Village has a density of 11242 People/Km², Kampung Lapai Village has a density of 15911 People/Km², Surau Gadang Village has a density of 8776 People/Km². km² and Kurao Pagang Village has a density of 4851 people/km². 3) Based on the significance value from the coefficient table, the value obtained is (0.11270679) or only 11% of population density influences or has a strong impact on health facilities in Nanggalo District.